Prognostic Value of the Pretreatment Neutrophil-to-Lymphocyte Ratio in Pediatric Parotid Cancer - Seng, Dongjie; Fang, Qigen; Li, Peng; Liu, Fei; Liu, Shanting (Frontiers in Pediatrics, 2019)
Objective: Our goal was to evaluate the prognostic significance of the neutrophil-to-lymphocyte ratio (NLR) in pediatric patients with parotid cancer. Materials and Methods: Pediatric patients with primary parotid cancer were retrospectively enrolled from several clinical centers. The associations between the clinical-pathologic variables and NLR and the prognostic significance of NLR for recurrence-free survival (RFS) and disease-specific survival (DSS) were analyzed. Results: A total of 123 patients were included. The mean NLR was 2.51 and ranged from 1.7 to 6.1. The tumor stage and disease grade were significantly related to NLR. In patients with NLR <2.51, the 10-year RFS rate was 97%, and in patients with NLR ≥2.51, the 10-year RFS rate was 84%; the difference was significant (p=0.016). In patients with NLR <2.51, the 10-year DSS rate was 98%, and in patients with NLR ≥2.51, the 10-year DSS rate was 83%; this difference was also significant (p=0.035). Further Cox model analysis confirmed the independence of NLR in predicting the RFS and DSS rates. Conclusions: NLR is significantly associated with prognosis in pediatric patients with parotid cancer.